Ubiquitous occurrence and functional dominance of comammox Nitrospira in full-scale wastewater treatment plants. (1st June 2023) - Zheng, Maosheng; Tian, Zhichao; Chai, Zimin; Zhang, Anqi; Gu, Ailu; Mu, Guangli; Wu, Dedong; Guo, Jianhua
Highlights: Comammox nitrospira ubiquitously occurred in WWTPs. Nitrospira nitrosa was the most dominant and active comammox species in WWTPs. MLSS and SRT determined niche separation of comammox nitrospira in sludge flocs. Comammox nitrospira functionally dominated ammonia oxidation in WWTPs. Abstract: The recent discovery of complete ammonia oxidation (comammox) bacteria has fundamentally upended the traditional two-step nitrification conception, but their functional importance in wastewater treatment plants (WWTPs) is still poorly understood. This study investigated distributions of comammox Nitrospira, ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA) in activated sludge samples collected from 25 full-scale WWTPs. Using quantitative PCR (qPCR) and 16S rRNA gene amplicon sequencing, our results revealed that comammox Nitrospira ubiquitously occurred in all of 25 WWTPs and even outnumbered AOB and AOA with an average abundance of 1∼183 orders of magnitude higher in 19 WWTPs. Moreover, DNA-based stable isotope probing (DNA-SIP) assays validated that comammox Nitrospira actively participated in ammonia oxidation in the three microcosms seeding with activated sludge from three typical WWTPs, in which the ratios of comammox amoA to AOB amoA were at the range of 1∼10, 10∼100 and >100, respectively. Phylogenetic analysis in heavy fractions further indicated that Nitrospira nitrosa ( N. nitrosa ) was the dominant and active species. We quantified the contribution of ammonia oxidizers based on the currently available kinetic parameters of the representative species and found that comammox made major contributions to ammonia oxidation than other nitrifiers (5 ∼ 106 times that of AOB). The findings not only demonstrate the ubiquitous occurrence of comammox, but also highlight their functional dominance in ammonia oxidation in WWTPs. Graphical abstract: Image, graphical abstract